The Linguistic Roots of the Doubled and the Three Letter Irregular Weak Verb: A Study in the Morphological Formation. The Book of Verbs as an Example (Journal of Misan Researches, 2021)
The phonological system is the base in the language structure, and then morphological system plays the role to get at the meaning intended. Thus this study is an attempt to come to know about the fact of the phonological and morphological correlation between the three-letter (trilateral) root geminated verb, which is built by doubling the middle radical form verb, and the trilateral mid-unsound verb. Hence, the researcher aims at examining the extent of the relationship between the tree-letter (trilateral) root geminated verb and the trilateral mid-unsound verb as far as the linguistic meaning is concerned. However, this is going to be conducted by setting forth the views of the and contemporary scholars as well as generating these verbs by the phonological inconsistency of doubling of the letters and the  vowel letters pursuant to the phenomenon of assimilation and replacement which takes place in some Arabic letters. However, this morphological phenomenon enriches the Arabic language to produce forms and verbs which have been unknown among the speakers of the language for the change and the generation are built on a base of an existence of a common rang from the sounds of the two words along with keeping the common meaning, though there is a different sound in the two words. Yet this had been studied in the book entitled kitab AL-Affl ( the book of verbs ) by Ibn Al-Qata'a as a sample for the study in question with an approach concerning the correspondence of the linguistic meaning between the two verbs dealt with in this study according to what has been dealt with and the results concluded.